Prevalence of microalbuminuria in type 2 diabetes mellitus at a diabetes centre in southern India. Issue 908 (1st June 2001) - Varghese, A; Deepa, R; Rema, M; Mohan, V
Abstract : OBJECTIVE: The aim of this study was to determine the prevalence and risk factors for microalbuminuria among south Indian type 2 diabetic patients attending a diabetes centre. METHODS: One thousand four hundred and twenty five type 2 diabetic patients attending a diabetes centre in south India were recruited for the study. Urinary albumin concentration was measured by immunoturbodimetric assay. Microalbuminuria was diagnosed if the urinary albumin excretion was >30 mg/g of creatinine. RESULTS: Overall prevalence of microalbuminuria was 36.3% (95% confidence interval 33.8 to 38.9). The prevalence of microalbuminuria increased with the increase in duration of diabetes. Multivariate regression analysis revealed age, diastolic blood pressure, glycated haemoglobin, fasting plasma glucose, and duration of diabetes to be associated with microalbuminuria. CONCLUSION: The overall prevalence of microalbuminuria in this south Indian clinic population and its risk factors are similar to that reported in Europeans.